Navigating Bureaucratic Challenges: Investigating the Interplay of Psychological Factors and Positive Outcomes in Public Sector Performance - Arbania Fitriani; Wihana Kirana Jaya; Sumaryono Sumaryono; Reni Rosari; Diana Fajarwati (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
This study investigates the psychological mechanisms underlying public sector employees’ behaviour by examining the moderating role of bureaucratic leadership (BL) in the relationship between public service motivation (PSM) and work engagement (WE), with WE acting as both a mediator and a predictor of affective organisational commitment (AOC) and innovative work behaviour (IWB). Using a quantitative approach, survey data were collected from 2,853 employees of Indonesian State-Owned Enterprises. We used Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine the direct effects and the mediating effects of WE, and the moderating effect of BL. The results emphasise that PSM has a strong positive effect on WE (β = 0.659, P < 0.001) but does not directly influence AOC (β = 0.023, P > 0.05) or IWB (β = 0.027, P > 0.05). WE fully mediates the relationship between PSM and both AOC (β = 0.412, P < 0.001) and IWB (β =0.344, P < 0.001). BL shows significant direct effects on WE (β = 0.169, P < 0.001), AOC (β = 0.186, P < 0.001), and IWB (β = 0.522, P < 0.001). In addition, BL moderates the relationship between PSM and WE at the 10 per cent significance level (β = 0.033, P < 0.10), indicating a context-dependent enabling role. This study extends the JD–R model in the public-sector context by highlighting the central role of WE.